2022
DOI: 10.3390/rs14102290
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Polarization Radar-Based Quantitative Precipitation Estimation of Mountain Terrain Using Multi-Disdrometer Data

Abstract: The precipitation systems that pass over mountains develop rapidly due to the forcible ascent caused by the topography, and spatial rainfall distribution differences occur due to the local development of the system because of the topography. In order to reduce the damage caused by orographic rainfall, it is essential to provide rainfall field data with high spatial rainfall accuracy. In this study, the rainfall estimation relationship was calculated using drop size distribution data obtained from 10 Parsivel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…R classes have an important impact on the performance of dual-polarization radar QPE estimators [53,55,69] as well as radar bands [53,55,69]. To quantify the performance of QPE estimators under different R classes and different radar bands, we used CC, RMSE, and NMAE to evaluate the performance of these QPE estimators in detail.…”
Section: Qpe Relations Under Different Rain Rate Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…R classes have an important impact on the performance of dual-polarization radar QPE estimators [53,55,69] as well as radar bands [53,55,69]. To quantify the performance of QPE estimators under different R classes and different radar bands, we used CC, RMSE, and NMAE to evaluate the performance of these QPE estimators in detail.…”
Section: Qpe Relations Under Different Rain Rate Classesmentioning
confidence: 99%
“…Furthermore, the performance of the dual-parameter estimators in the C-band was better than that in the S-and X-bands for all R classes, and the performance of the R(Z h ,Z dr ) estimator was better compared to the R(K dp ,Z dr ) estimator at lower R classes (C1 to C4, R less than 5 mm h −1 ), while the performance of the R(K dp ,Z dr ) estimator was better compared to the R(Z h ,Z dr ) estimator at higher rainfall rates (C5 to C6, R greater than 5 mm h −1 ) for the C-band. It is worth noting that previous studies have shown the importance of selecting suitable estimators for actual dual-polarization radar QPEs, and suitable estimators need to be provided for different regions and different band radars [55,[69][70][71]. For a dual-polarization radar QPE estimator in the Tianshan Mountains, we plan to conduct the relevant research based on dual-polarization radar observational data in the future.…”
Section: Qpe Relations Under Different Rain Rate Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is necessary to have simultaneous rainfall observations with higher temporal and spatial resolution. Polarimetric weather radars are preferred over rain gauges and satellites in producing Quantitative Precipitation Estimates (QPE) because of their ability to cover a larger spatial range and provide real-time rainfall information (You et al, 2022). Weather radars estimate rainfall by measuring the resulting reflectivity (Z) scattered by raindrops within a scanning volume measured in decibels relative to Z (dBZ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the metaheuristic optimization algorithms applied to structural optimization, the harmony search algorithm stands out as one of the most widely used techniques. Besides structural optimization, the harmony search technique has been applied to various areas of science and engineering such as transportation engineering [ 36 , 37 , 38 , 39 ], environmental engineering [ 40 , 41 ], healthcare systems [ 42 ], bioinformatics [ 43 , 44 , 45 ], and cloud computing [ 46 ].…”
Section: Introductionmentioning
confidence: 99%